Effects of the Supervisor-Supervisee Relationship on the Supervision’s Quality and the Scope of its Results (Brazilian Journal of Behavioral and Cognitive Therapy, 2023)
Supervision in psychotherapy is an intervention that aims to evaluate, improve and certify the performance of a colleague. The objective of this study was to investigate how supervision impacts the supervisor and the supervisee as professionals in ways that go beyond the goal initially set of promoting the supervisee’s clinical performance. Twenty clinical psychologists were interviewed, of which ten are supervisors and ten are supervisees. Speech fragments were coded and categorized following the tenets of grounded theory. Results suggest that the supervisor’s relational style influences the therapist’s learning process, generates new perspectives and helps to build the supervisee’s professional identity. The performance of the supervisee, the challenges encountered in practice, and the similarities between supervision and therapy drive supervisor’s growth in several dimensions. These results support an understanding of supervision as an interpersonal process of mutual influence.
Keywords: supervision; therapist training; behavioral therapies